ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI TANAMAN PADI DI DESA KERANJI PAIDANG KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - B01108054, HIPOLITUS FREDY AGUILAR (Jurnal Pembangunan dan Pemerataan, 2015)
This thesis is titled "Analisis Faktor-Faktor Yang Mempengaruhi Produksi Usahatani Tanaman Padi Di Desa Keranji Paidang Kecamatan Sengah Temila Kabupaten Landak" As for the issues discussed in this study are the factors that affect the production of rice plants and how efforts are being made to increase the production of rice plants in the Village District of Keranji Paidang Sengah Temila. This study aims to identify and analyze the factors that affect the production of rice plants and to determine the efforts made in improving the production of rice plants in the Village District of Sengah Temila Keranji Paidang. The method used in this study is a descriptive one, which describes the existing problems in the field later in the analysis in accordance with the facts. The technique of collecting data through direct observation with interviews, where the data collected is processed tabulated in the table. Based on the discussion made ​​it can be concluded that the results of the above calculations can be seen that labor, land, seeds, fertilizers and pesticides and significant effect on output of rice crops in the Village District of Sengah Temila Keranji Paidang, meaning that if labor increases it will increase production rice plant towards a positive, as well as the land area if done well and with the use of appropriate technology will also produce good output, while for the type of fertilizer, seeds and pesticides when used as fertilizers, seeds and pesticides are good and the right dose would increase agricultural output towards the better.